Porphyromonas gingivalis strain-dependent inhibition of uterine spiral artery remodeling in the pregnant rat. Issue 5 (18th May 2018) - Phillips, Priscilla; Brown, Mary B; Progulske-Fox, Ann; Wu, Xiao-Jun; Reyes, Leticia
Abstract: Porphyromonas gingivalis ( Pg ) is an important periodontal pathogen that is also implicated in pregnancy complications involving defective deep placentation (DDP). We hypothesized that Pg invasion of the placental bed promotes DDP. Pregnant rats were intravenously inoculated with sterile vehicle, Pg strain W83, or A7436 at gestation day (GD) 14 (acute cohort). Nonpregnant rats received repeated oral inoculations for 3 months before breeding (chronic cohort). Tissues and/or sera were collected at GD18 for analysis. Pg infection status was determined by seroconversion (chronic cohort) and by presence of Pg antigen in utero-placental tissues processed for histology and morphometric assessment of spiral artery remodeling. Mesometrial tissues from seropositive dams were analyzed for expression of interleukin 1β, 6, and 10, TNF, TGF-β, follistatin-related protein 3, and inhibin beta A chain since these genes regulate extravillous trophoblast invasion. The in situ distribution of W83 and A7436 antigen in utero-placental tissues was similar in both cohorts. In the acute cohort, mesometrial stromal necrosis was more common with W83, but arteritis was more common with A7436 infection ( P < 0.05). Increased vascular necrosis was seen in mesometrium of chronically infected groups ( P < 0.05). Only A7436-infected animals had increased fetal deaths, reduced spiral artery remodeling, reduced inhibin beta A expression, and an increased proportion of FSLT3 positive extravillous trophoblasts within spiral arteries. While infection with both Pg strains produced varying pathology of the deep placental bed, only infection with strain A7436 resulted in impaired spiral artery remodeling. Abstract : Invasion of the placental bed by Porphyromonas gingivalis impairs spiral artery remodeling and increases fetal loss in a microbial strain-dependent manner.